2021
DOI: 10.31219/osf.io/4kgu6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting and Defending Against Seizure-Inducing GIFs in Social Media

Abstract: Despite recent improvements in online accessibility, the Internet remains an inhospitable place for users with photosensitive epilepsy, a chronic condition in which certain light stimuli can trigger seizures and even lead to death in extreme cases. In this paper, we explore how current risk detection systems have allowed attackers to take advantage of design oversights and target vulnerable users with photosensitivity on popular social media platforms. Through interviews with photosensitive individuals and a c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Marriott et al found that there is no research at all that engages motor accessibility [MLB∗21]. We have found 2 papers that engage cognitive/neurological disability in visualization and 1 student poster from IEEE Vis, which are all recent (specifically intellectual developmental disabilities [WPA∗21] and seizure risk [SB20,SSB21]). We found no papers that engage vestibular accessibility, such as motion and animation‐related accessibility.…”
Section: Existing Work In Data Visualization and Accessibilitymentioning
confidence: 99%
“…Marriott et al found that there is no research at all that engages motor accessibility [MLB∗21]. We have found 2 papers that engage cognitive/neurological disability in visualization and 1 student poster from IEEE Vis, which are all recent (specifically intellectual developmental disabilities [WPA∗21] and seizure risk [SB20,SSB21]). We found no papers that engage vestibular accessibility, such as motion and animation‐related accessibility.…”
Section: Existing Work In Data Visualization and Accessibilitymentioning
confidence: 99%
“…Research on accessibility for people with photosensitivity has primarily focused on detecting seizure-inducing content in GIFs [53] and videos [4,7,18], as both media types have been used to orchestrate malicious attacks against people with photosensitivity on social media (e.g., [3,16,33,46]). The previously mentioned tool PEAT [19] is widely used for checking the safety of videos posted to the internet, while the Harding Flash and Pattern Analyzer [56] is used by broadcast companies to ensure videos shown on television are photosensitivesafe.…”
Section: Accessibility For Photosensitivitymentioning
confidence: 99%
“…Each screen recording was then tested for seizure-inducing content [19], an open-source photosensitive risk detection system. PEAT is the industry standard for detecting dangerous flashes in videos and is often used as a benchmark in scientific studies involving the photosensitive risk (e.g., [2,4,53]). The procedure used to create all of the screen recordings is included in the Supplemental Material.…”
Section: Preliminary Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that photosensitive risk is strongly correlated with the area of retina stimulated by the strobing or flashing content [9], so it is likely that content that is safe when viewed on a laptop or phone could become seizure-inducing when viewed in an immersive VR context that stimulates a larger percentage of the retina. Interview participants with photosensitivity have described a low-tech solution they use for mitigating seizure-inducing content on a phone or laptop, which is to quickly remove the offending device by shutting the laptop or throwing the phone away from [20]. Getting away from the dangerous content is more involved when the user is wearing a VR headset, making it even more important to establish protective systems within VR software to automatically detect and block seizure-inducing content.…”
Section: Seizure-inducing Content In Virtual Realitymentioning
confidence: 99%